PEMANFAATAN LIGNIN HASIL ISOLASI DARI LINDI HITAM PROSES BIOPULPING BAMBU BETUNG (Dendrocalamus asper) SEBAGAI MEDIA SELEKTIF JAMUR PELAPUK PUTIH - Sita Heris Anita; Dede Heri Yuli Yanto; Widya Fatriasari (BRIN Publishing, 2011)
The utilization of black liquor produced in pulp and paper production has been limited for adbesive. In microbiology, black liquor can be used as a selective mediunt. The purpose of this study was to evaluate the performacne of lignin isolated from black liquor of biopulping process as a selective medium for white-rot fungi. Lignin, from black Liquor of soda and kraft pulping of bamboo petung was isolated by acid addition. Lignin solid was then purified using diccan solution, weighted and qualitatively analyzed using a spectrophotometer. The isolated lignin was added to agar media to test the white-rot fungi selectivity (Phanerochazte crysosporium and Trametes versicolor). The results showed that pretreatment of bamboo for 30 days give more lignin than the 45-days treated bambon. Lignin solid from kraft process was also bigher than lignin from soda process. Enzyme secretion from fungi T. versicolor occurs more rapidly than P. chrysasporium on selective media alkali-lignin.